VARIABILITY AND HERITABILITY STUDIES FOR POD YIELD AND ITS COMPONENT CHARACTERS IN WINGED BEAN [PSOPHOCARPUS TETRAGONOLOBUS (L.) DC.] - K. PRASANTH; I. SREELATHA KUMARY (The Bioscan, 2014)
In the present investigation, twenty one genotypes of winged bean were evaluated to estimate variability, heritability and genetic advance over mean for vegetable pod yield and related attributes during 2013-14 under Kerala conditions. The analysis of variance showed significant difference among all the genotypes for yield and its attributing traits studied. The results indicated that the traits viz., primary branches per plant (79.32, 39.52), days to first flowering (93.68, 49.62), days to 50 per cent flowering (96.60, 49.95), days to first harvest (95.15, 38.50) and pod weight (78.79, 28.43) exhibited high heritability (Ã 60 %) coupled with high to moderate genetic advance as percent mean indicates the presence of flexible additive gene effects, which may be improved through simple plant selection methods. While, the remaining traits showed high to moderate heritability (30-60) coupled with moderate (10-20) to low (<10) genetic advance as percent of mean, suggesting predominance of nonadditive gene action in the expression of the traits, therefore may be potentially utilized in recombination breeding. Furthermore, based on the genetic parameters and per se performance, the suitable genotypes for these traits could be isolated and utilized for various winged bean improvement programmes.